First Report of stem rot in Cymbidium sinense Caused by Fusarium oxysporum (FOSC) in China - Liang, Peng-Yu (Plant disease, 2022)
Cymbidium sinense (Jackson ex Andr.) Willd is a perennial terrestrial plant in the orchid family mainly distributed in China, Japan, India and Southeast Asia that occupies a strong position in the flower market due to its bright green leaves and fragrant flowers (Zhang et al. 2013). Cymbidium sinense is not only valued by people for its ornamental and economic value, but its roots have antiasthmatic medicinal properties (Ke et al. 2004). In August 2020, about 15% stem rot on two-year old C. sinense with varying severity was observed in five nursery gardens located in Enshi city (N 30° 16', E 109° 29'), Hubei province, China. Typical symptoms of C. sinense included roots and inner part of the pseudobulbs changing from white to brown and rotting. Leaves became brown and withered from bottom to top, and there was an obvious blight yellow halo at the junction of diseased and healthy tissue, which eventually caused the whole plant to wilt and die (Fig. 1d). To isolate the pathogen, a total of 15 leaf tissues from the disease-health junction (3 × 3 mm) from 5 individual plants (3 leaves/plant) with symptoms were surface sterilized with 75% ethanol for 30 s and 2% sodium hypochlorite (NaOCl) for 3 min. The sterilized tissue was rinsed three times with sterilized water, and then placed on potato dextrose agar (PDA) for incubation at 28°C in the dark for 5 days. Isolated colonies were subcultured by a hyphal tip protocol. Thirteen fungal isolates were obtained. Through preliminary pathogenicity tests, we found that ten isolates induced leaf blight. These ten isolates with pathogenicity showed similar morphological characteristics, with initial white-flocculent aerial mycelium that secreted a lavender pigment and produced colonies with an irregular edge after 3 days on PDA. The ten strains were cultured on PDA plates at 28℃ for 5 and 15 days to observe colony and conidial characteristics. The ten strains were identified as Fusarium based on morphological characteristics (Leslie and Summerell 2006). Strain ML0303 was selected for further identification. Macroconidia were falciform, hyaline, slightly pointed at both ends with two to four septa, 24.0 ± 5.6 µm × 4.7 ± 0.8 µm (n = 50). Microconidia were hyaline, oval, globose, with zero to one septum, 5.5 ± 1.3 µm × 2.2 ± 0.5 µm (n = 50) (Fig. 1c). Total genomic DNA of strain ML0303 was extracted with a CTAB protocol (Stenglein and Balatti 2006). The translation elongation factor (EF-1α), RNA polymerase II second largest subunit (RPB2) and β-tubulin (Tub2) genes were amplified respectively using primer pairs EF1/EF2, RPB2-5F2/RPB2-7cR and T1/T22 respectively (O'Donnell. et al. 2010, O'Donnell. et al. 1997). The EF-1α, RPB2 and Tub2 (accession numbers-MW719874, OL614838, OL689398, respectively) gene sequences were submitted to GenBank. EF-1α, RPB2 and Tub2 sequences of ML0303 showed 99.5% - 100% identity respectively with Fusarium oxysporum in the Genbank and FUSARIUM-ID databases. The multilocus sequence data was used to infer a phylogenetic tree via a Neighbor-joining (NJ), Maximum-likelihood (ML) and Maximum-Parsimony(MP) together with reference sequences from GenBank. The topology of the three trees was similar; only the NJ tree is presented here. Strain ML0303 and F. oxysporum formed a clade supported with high values (NJ/ML/MP: 96,95,97). The results indicated that the fungus was F. oxysporum based on the phylogenetic analysis and BLASTn queries. For pathogenicity tests, conidia of strain ML0303 were collected by rinsing PDA plates. Two-year-old C. sinense grown in plastic pots filled with sterilized autoclaved sandy loam soil were used for the tests. Three pots (two plants/pot) were included in each treatment. Spore suspensions (106spores/ml) of strain ML0303 were used to irrigate the stem-zone of the plants, and sterile water was used as control. The two treatments were placed in a greenhouse and incubated at 28±2℃ with a 14-hour light/10-hour dark cycle. The experiment was repeated twice. After three weeks, stem rot symptoms were observed on C. sinense inoculated with ML0303, that were the as same as observed in the nursery (Fig. 1e-h). No symptoms were observed on the negative control. Fusarium oxysporum was re-isolated from the infected plants to fulfill Koch's postulates. Partial EF-1α and RPB2 gene sequences were used for molecular identification. Members of the FOSC are notorious for causing many diseases, which includes stem rot of Sulcorebutia heliosa and root rot of Torreya grandis (Garibaldi et al. 2020; Zhang et al. 2016). To our knowledge, this is the first report of stem rot by F. oxysporum on C. sinense in China. The finding of this pathogen provides a clear target for stem rot control